The Atkins 100 eating solution : easy, low-carb living for everyday wellness - Heimowitz, Colette (Atria Paperback, 2020)
"From the creators of the original ketogenic, low-carb diet, comes the most accessible and flexible approach to the Atkins diet ever: a simplified lower carb and sugar approach based on solid science"--